Oral Lisinopril Raises Tissue Levels of ACE2, the SARS-CoV-2 Receptor, in Healthy Male and Female Mice - Brooks, Steven D.; Smith, Rachel L.; Moreira, Aline S.; Ackerman, Hans C. (Frontiers in Pharmacology, 2022)
Angiotensin-converting enzyme 2 (ACE2) is the established cellular receptor for SARS-CoV-2. However, it is unclear whether ACE1 inhibitors (e.g., lisinopril) or angiotensin receptor blockers (e.g., losartan) alter tissue ACE2 expression. This study sought to determine whether lisinopril or losartan, as monotherapies or in combination, change tissue levels of ACE2 in healthy male and female mice. Mice received lisinopril (10 mg/kg/day), losartan (10 mg/kg/day), or both for 21 days via drinking water. A control group received water without drug. ACE2 protein index (ACE2 protein / total protein) was determined on small intestine, lung, kidney, and brain. Oral lisinopril increased ACE2 protein index across all tissues (p < 0.0001 vs control). In contrast, the combination of lisinopril plus losartan did not increase ACE2 levels in any tissue (p = 0.89 vs control) and even decreased tissue expression of the Ace2 gene (p < 0.001 vs control). Tissue ACE2 remained elevated in mice 21 days after cessation of lisinopril (p = 0.02). Across both cohorts, plasma ACE2 did not correlate with ACE2 protein index in any tissue. A sex difference was observed: kidney ACE2 levels were higher in males than females (p < 0.0001). Oral lisinopril increases ACE2, the cellular receptor for SARS-CoV-2, in tissues that are relevant to the transmission and pathogenesis of COVID-19. Remarkably, the addition of losartan prevented lisinopril-induced increases in ACE2 across tissues. These results suggest that ACE inhibitors and angiotensin receptor blockers interact to determine tissue levels of ACE2.